2015
DOI: 10.1016/j.foodchem.2015.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and dual physical modifications on pinhão starch

Abstract: Pinhão starch was modified by annealing (ANN), heat-moisture (HMT) or sonication (SNT) treatments. The starch was also modified by a combination of these treatments (ANN-HMT, ANN-SNT, HMT-ANN, HMT-SNT, SNT-ANN, SNT-HMT). Whole starch and debranched starch fractions were analyzed by gel-permeation chromatography. Moreover, crystallinity, morphology, swelling power, solubility, pasting and gelatinization characteristics were evaluated. Native and single ANN and SNT-treated starches exhibited a CA-type crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 38 publications
5
55
0
1
Order By: Relevance
“…The native pinhão starch granules showed a mixture of rounded and oval shapes, with smooth surface, without the presence of pores, but some depressions, results also found by Pinto et al The native corn starch has a polygonal shape with well‐defined borders, as reported by Zhang et al, with some granules having a porous surface and others with a rounded shape and smaller (<7 μm) size (Figure ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The native pinhão starch granules showed a mixture of rounded and oval shapes, with smooth surface, without the presence of pores, but some depressions, results also found by Pinto et al The native corn starch has a polygonal shape with well‐defined borders, as reported by Zhang et al, with some granules having a porous surface and others with a rounded shape and smaller (<7 μm) size (Figure ).…”
Section: Resultssupporting
confidence: 77%
“…The starch is composed of two different glucose polymers: amylose and amylopectin . Besides, can be found lipids, minerals and nitrogenated compounds, which may influence the starch characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…XRD diffraction measurement was performed to check the crystallinity of starch, with the results shown in Figure . As we can see here, all the starch samples in the form of granules had diffraction peaks at 15°, 17°, 18°, and 23°, indicting a typical A‐type crystallization . This means that the chemical modification occurred mainly in the amorphous region of the granule and did not alter the crystal pattern of starch.…”
Section: Resultssupporting
confidence: 51%
“…Starch crystallinity is classified into A, B, and C difractogram patterns . All treated starches showed B type XRD (Figure ), characterized by a peak at 17° (2Θ), followed by small peaks at 15, 20, 22, and 24° (2Θ) and a typical peak at 5.6° (2Θ) . Differently to cassava starch, which presented crystallinity pattern A type, with high peaks at 15 and 23° and smaller peaks 17° and 18°, including the absence of peak at 5.6° (2Θ) (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Starches have been used for varied applications from food to chemicals. The main starch sources in particular for food uses is maize, cassava, potato, wheat, and rice, however non‐conventional starches have gained recent interest due to their physicochemical characteristics with the potential of replacing chemically modified starches that generates chemical waste.…”
Section: Introductionmentioning
confidence: 99%